Statistical Characterization of κμ Shadowed Fading - Paris, Jose F. (IEEE transactions on vehicular technology, 2014)
This paper investigates a natural generalization of the κ - μ fading channel in which the line-of-sight (LOS) component is subject to shadowing. This fading distribution has a clear physical interpretation and good analytical properties and unifies the one-side Gaussian, Rayleigh, Nakagami- m, Rician, κ - μ, and Rician shadow fading distributions. The three basic statistical characterizations, i.e., probability density function (pdf), cumulative distribution function (cdf), and moment-generating function (mgf), of the κ - μ shadowed distribution are obtained in closed form. Then, it is also shown that the sum and maximum distributions of independent but arbitrarily distributed κ - μ shadowed variates can be expressed in closed form. This set of new statistical results is finally applied to modeling and analysis of several wireless communication systems, e.g., the proposed distribution has applications to land mobile satellite (LMS) communications and underwater acoustic communications (UAC).